Angels and demons in art - Giorgi, Rosa.; Zuffi, Stefano, 1961-; Giammanco Frongia, Rosanna M. (Los Angeles : J. Paul Getty Museum, 2005)
This illustrated volume analyzes artists' representations of angels and demons and heaven and hell from the Judeo-Christian tradition and describes how these artistic portrayals evolved over time. As with other books in the Guide to Imagery series, the goal of this volume is to help decode the symbolic meanings in the masterworks of Western Art. The first chapter traces the development of images of the Creation and the Afterworld from descriptions of them in the scriptures through their evolution in later literary and philosophical works. The following two chapters examine artists' depictions of the two paths that humans may take, the path of evil or the path of salvation, and the punishments or rewards found on each. A chapter on the Judgment Day and the end of the world explores portrayals of the mysterious worlds between life and death and in the afterlife. Finally, the author looks at images of angelic and demonic beings themselves and how they came to be portrayed with the physical attributes-wings, halos, horns, cloven hooves-with which we are now so familiar.
Creation and the geography of the next world -- The path of evil -- The path of salvation -- The last days: judgment and reality -- The infernal cohorts -- The angelic cohorts.
Translation of: Angeli e demoni.
Includes indexes.
Translated from the Italian.
Translated from the Italian.
Keywords: Angels in art -- Dictionaries; Devil in art -- Dictionaries; Christian art and symbolism -- Dictionaries; Supernatural in art -- Dictionaries